Improvement of thermal resistance in InGaAs/GaAs/AlGaAs microdisk lasers bonded onto silicon. (1st July 2022) - Zubov, F I; Moiseev, E I; Nadtochiy, A M; Fominykh, N A; Ivanov, K A; Makhov, I S; Dragunova, A S; Maximov, M V; Vorobyev, A A; Mozharov, A M; Mintairov, S A; Kalyuzhnyy, N A; et al.
Abstract: Epi-side down bonding on a silicon substrate of AlGaAs/GaAs microdisk lasers is presented. A heterostructure with coupled large optical cavities enables location of an InGaAs quantum dot active region at a distance of ∼1 µ m from the heterostructure surface. The thermal resistance was reduced to 0.2 and 0.1 K mW −1 for disks of 30 and 50 µ m in diameter, respectively. The maximum continuous-wave power limited by the thermal rollover is more than doubled after bonding.